Hard and soft materials: putting consistent van der Waals density functionals to work. (12th January 2022) - Frostenson, Carl M; Granhed, Erik Jedvik; Shukla, Vivekanand; Olsson, Pär A T; Schröder, Elsebeth; Hyldgaard, Per
Abstract: We present the idea and illustrate potential benefits of having a tool chain of closely related regular, unscreened and screened hybrid exchange–correlation (XC) functionals, all within the consistent formulation of the van der Waals density functional (vdW-DF) method (Hyldgaard et al (2020 J. Phys.: Condens. Matter 32 393001)). Use of this chain of nonempirical XC functionals allows us to map when the inclusion of truly nonlocal exchange and of truly nonlocal correlation is important. Here we begin the mapping by addressing hard and soft material challenges: magnetic elements, perovskites, and biomolecular problems. We also predict the structure and polarization for a ferroelectric polymer. To facilitate this work and future broader explorations, we present a stress formulation for spin vdW-DF and illustrate the use of a simple stability-modeling scheme. The modeling supplements density functional theory (DFT) (with a specific XC functional) by asserting whether the finding of a soft mode (an imaginary-frequency vibrational mode, ubiquitous in perovskites and soft matter) implies an actual DFT-based prediction of a low-temperature transformation.